Edukasi Masyarakat Jatirejo Mojosongo dalam Meningkatkan Perekonomian melalui Budidaya Maggot Berbasis IoT untuk Pengolahan Sampah Organik: Educating the Jatirejo Mojosongo Community in Improving the Economy through IoT-based BSF Cultivation for Processing Organic Waste - Sollikah, Anisa Ayu; Arifin, Muhammad Fatkhi Futukhal; Sunyahni, Desi; Muchti, Elnawawi; Sumawang, Slash Arthur Edi; Farihin, Miftahul; Arrasyid, Akhmad Yusron; Anshoriah, Kurnia; Prasetyo, Ridwan Himawan; Kusuma, Anila (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Organic waste makes up the lion's share of solid waste generated by human activities. Therefore, organic waste management efforts are needed to help solve it. One of the efforts that can be made is using BSF larvae to decompose organic waste. BSF larvae or maggots have a high protein and fat content, a chewy texture, and the ability to secrete natural enzymes. BSF females can lay up to 400-800 eggs. After 3-4 days, the eggs will hatch into larvae and consume organic waste, including various types of organic waste such as kitchen, fruits, vegetables, fish, urban, human, and animal waste. The flexibility of BSF larval feed facilitates the cultivation process, and it becomes an ideal insect for decomposing organic waste and becomes a business field because of its fat and protein content. The method of decomposing litter using BSF larvae is quite promising because the opportunities are quite promising, but it is still completely manual. Therefore, IoT-based maggot cultivation, an innovation in maggot cultivation, is needed. IoT design is placed at the maggot breeding stage, with optimal temperature, humidity, and light intensity conditions. This breeding ground is equipped with Arduino, humidity, and temperature sensors to regulate and maintain the best state in each larval breeding process until it becomes a pupa. This design is expected to provide convenience and increase the yield of maggot cultivation.